Characterization of a VRC01-like antibody lineage with immature VL from an HIV-1 infected Chinese donor. (February 2023) - Hu, Yuanyuan; Li, Dan; Yuan, Zhenzhen; Feng, Yi; Ren, Li; Hao, Yanling; Wang, Shuo; Hu, Xintao; Liu, Ying; Hong, Kunxue; Shao, Yiming; Wang, Zheng
Abstract: Because of the broadly neutralizing activity, VRC01-class antibodies are attractive templates for HIV-1 vaccine development and suitable candidates for HIV-1 therapy. Although we previously revealed that glycans in gp120 may have a role in the uneven evolution of the VH and the VL of a VRC01-class antibody, DRVIA7, which was isolated from an elite neutralizer, it is unknown whether the immature VH or VL of VRC01-class antibodies are also present in the non-neutralizer. We identified a CD4bs-directed antibody – 263A9 – with low neutralizing activity from a donor whose plasma had a moderate neutralizing spectrum in this study. The 263A9 antibody, in particular, was a VRC01-like antibody whose VH and VL were derived from IGHV1–2 * 04 and IGKV1–33 * 01, respectively, and both had significant SHM rates. Surprisingly, we discovered that the VL of 263A9 hindered the neutralizing activity of the antibody, and that replacing its LCDR1 and LCDR3 with VRC01 increased the neutralizing breadth of the chimeric antibodies. Following that, an antibodyomics research revealed that the VL of 263A9 lineage was remote from VRC01-class antibodies. We also looked at the envelope sequence characteristics of donor CBJC263 and discovered that N276 in the D loop and N460/N463 glycans in the V5 region of gp120 potentially interact with VL of 263A9 at the structural level. This study will provide valuable information for immunogen screening and vaccine development for eliciting VRC01-class antibodies. Data availability statement: The original data presented in the study are included in the article or Supplementary materials . Further inquiries can be directed to the corresponding author. HIV Env sequences in the manuscript had been deposited into the GenBank with the accession numbers from OL466822 to OL466859. Highlights: We isolated a CD4bs-directed antibody, 263A9, which VL hindered its neutralizing activity. Paring heavy chain of 263A9 with light chain of VRC01 produced broadly neutralizing antibody. Replacing LCDR1 and LCDR3 of 263A9 with VRC01 increased the neutralizing breadth of the chimeric antibodies.